Saturated red phosphorescent Iridium(III) complexes containing phenylquinoline ligands for efficient organic light-emitting diodes. (August 2020) - Ding, Yong; Liu, Di; Li, Jiuyan; Li, Huiting; Ma, Haiyang; Li, Deli; Niu, Rui
Abstract: Saturated red iridium phosphors are strongly desired for application in organic light-emitting diodes (OLEDs). Most of the reported iridium complexes with 2-arylquinoline or its derivatives as cyclometalating ligands are orange-red phosphorescent with peak wavelength below 620 nm. Herein trifluoromethyl (CF3 ) or Fluorine (F) is introduced into the 6-site of quinoline ring to design and synthesize the cyclometalated ligands 2-phenyl-6-CF3 /F-quinoline (CF3 -phq or F-phq) and heteroleptic iridium complexes Ir(CF3 -phq)2 (acac) (Ir-1), Ir(CF3 -phq)2 (tmd) (Ir-2), Ir(F-phq)2 (acac) (Ir-3) and Ir(F-phq)2 (tmd) (Ir-4). Owing to the electron-deficient feature of CF3 and F, the electron affinity of these complexes are increased, the corresponding LUMOs are pulled downwards, and the phosphorescence of CF3 -containing iridium complexes are saturated red with peaks at 627–632 nm in photoluminescence. At the same time, by varying the ancillary ligand from acetylacetonate (acac) to 2, 2, 6, 6-tetrametylheptane-3, 5-dionate (tmd), the emitting performance are dramatically improved. As a result, the Ir(CF3 -phq)2 (tmd) based red OLED realized pure red electroluminescence with Commision Internationale de L'Eclairage (CIE) coordinates of (0.67, 0.33) with a high brightness of 12695 cd m −2 and a maximum external quantum efficiency of 14.96%, respectively, which maintained as high as 9.62% at a practical luminance of 1000 cd m −2 . This is the first example of saturated red iridium phosphors with structure modification at the 6-site of quinoline ring of 2-phenylquinoline ligand. Graphical abstract: By incorporating electron-withdrawing fluorine (-F) or trifluoromethyl (-CF3 ) at the 6-site of quinoline ring of the 2-phenyl-quiniline cyclometalating ligands and changing the auxiliary ligand from acac to bulky tmd, the heteroleptic iridium complexes realize pure red phosphorescence with CIE coordinates of (0.67, 0.33) and high efficiency of 14.96% in doped organic light-emitting diodes, which still remains at 9.62% at a practical brightness of 1000 cd m −2 . Image 1